Flexural behaviour of externally prestressed beams. Part II: Experimental investigation - Chee, Khoon Ng; Kiang, Hwee Tan (Elsevier Ltd., 2006)
In Part I of this paper, a simple “pseudo-section analysis” method which accounts for second-order effects in a simply supported, externally prestressed beam subjected to two symmetrically applied concentrated loads was developed. In this paper, an experimental investigation of the flexural behaviour is reported. A total of nine simply supported prototype beams were tested to evaluate the effect of span-to-depth ratio and second-order effects. It was found that span-to-depth ratio has no significant effect on the flexural behaviour of the beams. For beams with span-to-depth ratio of up to 22.5, a single deviator provided at midspan section is effective in minimising second-order effects, that is, maintaining higher load-carrying capacity and ensuring ductility at the ultimate limit state for the beams. However, second-order effects prevailed in a longer beam with larger span-to-depth ratio of 30.0 despite the provision of a single deviator at midspan. This type of long beams would require at least two deviators placed at one-third span sections, hence reducing the deviator spacing in order to minimise second-order effects so that the beams would achieve the desired flexural performance with regard to beam strength and ductility. Theoretical predictions of the load–deformation responses using the proposed analytical model were found to agree well with the test results in this study and experimental data of other investigations.